PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA GURU DENGAN LINGKUNGAN KERJA DAN KEPUASAN KERJA SEBAGAI VARIBEL INTERVENING PADA GURU SMA DI KECAMATAN DEWANTRAA KABUPATEN ACEH UTARA - Nurlaili Nurlaili; Apridar Apridar; Aiyub Aiyub (J-MIND (Jurnal Manajemen Indonesia), 2020)
This study aims to determine the effect of organizational culture and leadership style on teacher performance with work environment and job satisfaction as an intervening variable. The data used are primary data by distributing questionnaires to 140 respondents, namely teachers who teach at Senior High Schools in Dewantara District, North Aceh Regency. The method used to analyze the data is Structural Equation Modeling (SEM). The results of the study found that the organizational culture and work environment had a positive and significant effect on the work environment and job satisfaction of senior high school teachers in Dewantara District, North Aceh Regency. Furthermore, found organizational culture, leadership style, work environment and job satisfaction have a positive and significant effect on the performance of high school teachers in Dewantara District, North Aceh Regency. Furthermore, it was found that work environment variables and job satisfaction mediate fully the influence of organizational culture and leadership style on the performance of high school teachers in Dewantara District, North Aceh Regency. Based on the results of these studies it is expected that the leaders or principals in Dewantara Subdistrict, North Aceh Regency be able to give attention and priority in institutionalizing organizational culture and creating a conducive work environment to improve job satisfaction and teacher performance. Keywords: organizational culture, leadership style, work environment, job satisfaction and teacher performance